Determination of bovine and porcine gelatin polypeptides using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) - Tukiran, Nur Azira (2012)
Gelatin is used widely in food and pharmaceutical industries because of its unique physicochemical characteristics. However, the gelatin utilisation becomes an issue among Muslim, Jews and vegetarians due to its animal origin. As such, methods of gelatin detection and differentiation as well as gelatin stability in the processed foods have emerged as an important research area to be studied. Therefore, the aim of this study was to detect and differentiate the bovine and porcine gelatin polypeptides using a combination method of sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and Principal Component Analysis (PCA). Utilising optimal conditions of SDS-PAGE with 6% of resolving gel, 8 μg amount of protein, 8 M Urea-SDS sample buffer, together with sensitive silver staining had exhibited molecular weights of gelatin polypeptides ranged from 53 to 220 kDa. They can be used to differentiate between bovine and porcine gelatins. The gelatin of porcine exhibited wider molecular weight distribution as compared to bovine that consisted of 11 and 2 prominent bands, respectively. In addition, these prominent bands were stable under heat treatment and consistent even in different Bloom number offer suitability for the identification of gelatin sources. In order to determine the detection limit of SDS-PAGE in detecting the percentage of adulterated samples,PCA was applied to classify the percentage of adulteration in the samples. Results showed that SDS-PAGE combined with PCA was unable to detect the presence of less than 5% porcine gelatin adulterated in the bovine gelatin. To detect the presence of gelatin in the samples, both extracting solutions (cold acetone and deionised water) are suitable; however, for commercial processed products with mixed ingredients cold acetone was more efficient. In the study, the qualitative comparison using SDS-PAGE between samples could be differentiated by PCA, and the combination may provide robust information for gelatin species identification. This study proposed that this new approach employing SDS-PAGE and PCA together with a simple gelatin extraction method may provide a useful tool for food authenticity issues concerning gelatin.